’At overskue, tilfredsstille og lyksaliggjøre’ - Damsholt, Tine (K&K - Kultur og Klasse, 2016)
Taking its point of departure in Foucault’s analysis of the notions of ‘reason of state’ and ‘police’ i.e. Polizeiwissenschaft in eighteenth-century Europe, the article investigates the complex understanding of happiness and bliss in a Danish parish topography from 1795. The notions of happiness and bliss are entangled with the emergence of ‘the political problem of population’ in which the population appears as an entity that must be governed according to its specific ‘nature’. Thus, the population appears as a new object of study and as purchase for interventions addressing living conditions as well as ways of acting and living. The parish topography by Nils Blicher is inscribed in this rationale that tends to increase the power of the state by making good use of its forces, to obtain the welfare of the population; to make their lives comfortable and to provide them with the things they need for their livelihood. Blicher’s description of the life and conditions of the peasantry is replete with suggested solutions to the problems described. And among the main objects to be concerned with are health and production, but also the happiness of the population. However, his understanding of happiness and bliss goes beyond the reason of the state and is completed with a Christian understanding of heavenly bliss.